Relações filogenéticas entre isolados fúngicos de Cyrtopodium saintlegerianum Rchb. f., de Epidendrum nocturnum Jacq. (Orchidaceae) e de Rhizoctonia spp. Fitopatogênicas ao arroz e ao feijão - Luzini, Aline Pereira (2013)
The orchids Cyrtopodium saintlegerianum (epiphyte) and Epidendrum nocturnum (rupicola) occur in areas anthropized of cerrado and cerrado rupestre, respectively. Even though, Rhizoctonia sp. is pathogenic to various crops, it is one of the more frequent genera among the microrrhizal fungi. Studies on fungal phylogenetics utilizing the ITS (Internal Transcribed Spacer) region of rDNA are important for evaluating specificity between plant and fungus, the evolutionary history of species and host - pathogen interactions. The objective of the present study include molecular characterization and establishment of phylogenetic relationships among endophytic/micorrhizal fungi isolates of C. saintlegerianum and of E. nocturnum pertaining to genera Rhizoctonia sp., Xylaria sp. and isolates of Rhizoctonia spp. pathogenic to rice and common beans and of isolates obtained from Genbank. The genomic DNA of one micorrhizal isolate, two of Xylaria sp. (endophytic), and four of rice and bean pathogens were extracted, and soon after sequencing of ITS 1 and ITS2 of nrDNA was done. The phylogenetic relations, inferred by Bayesian analysis among the rhizoctonia-like isolates of the present study and found in GenBank showed three clusters, and Xylarioides showed one cluster. The molecular results of micorrhizal Rhizoctonia sp. and Xylariodes are in close agreement with the results on morphology. The micorrhizal isolates formed one poliphyletic clad with the isolates of the GenBank. The micorrhizal isolate of Rhizoctonia sp. obtained from E. nocturnum formed one lineage different from Rhizoctonia spp. originating from other orchid species of GenBank. The Xylarioides isolates obtained in the present study showed lineage different of the found in GenBank.